INTERNSHIP AT THE WYANDOTTE COUNTY HEALTH DEPARTMENT - Cavlovic, Emily (My University, 2016)
This report is a summation of my field experience conducted at the Unified Government Public Health Department from May 31st to July 15th, 2016. I specifically worked at the Communicable Disease Control Program I also interacted with other sections of the health department. The main project consisted of increasing the reporting of animal bites in Wyandotte County in order to conduct more accurate and timely rabies surveillance in this County. This involved updating of current animal bite reporting protocols and rabies information, and improving access to the Communicable Disease Control webpage. During this internship, I also conducted projects that focused on increasing communication between the Communicable Disease Control Program and the residents of Wyandotte County. Overall, I learned about how a local public health department operates and strives to better the health of residents in a community.
Keywords: Animal bites; Health communication; Public health; Rabies; Wyandotte County Kansas